Emodin Alleviates Lupus Nephritis in Rats by Regulating M1/M2 Macrophage Polarization. (4th February 2023) - Xiong, Weijian; Li, Ying; Zhang, Ling; Xiong, Yanying; Zhong, Jin; Li, Xunjia; Luo, Yan; Liu, Hong; Kang, Renhong; Chen, Yunjie
Abstract : Lupus nephritis (LN) is one of the most common clinical manifestations of systemic lupus erythematosus (SLE), causing death and disability. The current research study explored whether there was any improvement effect on LN after emodin administration. Network pharmacology was used to screen the target genes of emodin for the treatment of LN. LPS and IL-4 were employed for RAW264.7 macrophage M1/M2 polarization induction, and 0.1% HgCl2 was used for the LN rat model's establishment. Flow cytometry was performed to detect the effect of 20, 40, and 80  µ M emodin on RAW264.7 macrophage polarization. HE and PAS staining were subsequently conducted to detect 70 mg/kg emodin action on renal injury in LN rats. The effect of emodin on the content of urinary proteins and dsDNA antibodies was also determined. The results indicated that peroxisome proliferators-activated receptors gamma (PPARG) may be a target gene of emodin in LN, and emodin had no significant toxicity to macrophages at different concentrations. Compared with the control, emodin significantly inhibited LPS-induced polarization in M1 macrophages and improved that of IL-4-induced M2 macrophages. Besides, emodin alleviated kidney injury and markedly reduced the levels of urinary protein and dsDNA antibodies in rats. Moreover, after targeting interference with the PPARG expression, the improvement effect of emodin on LN is significantly reduced, indicating that emodin may relieve the symptoms of LN by activating the PPARG expression. Our study revealed that PPARG may be applied as a new therapy for LN.